A Giant Coronary Aneurysm in a Suspected Kawasaki Disease Causing Asymptomatic Myocardial Ischemia - Mondal, Sudipta; Walse, Rohit; Pant, Bhagwati Prasad; Abhilash, Sreevilasam P.; Sasidharan, Bijulal (Indian Journal of Radiology and Imaging, 2023)
Coronary involvement in Kawasaki disease is not uncommon; however, giant coronary aneurysm exceeding 50 mm is extremely rare. In this article, we presented a case of giant coronary aneurysm involving right coronary artery with associated asymptomatic myocardial ischemia as evident by multimodality imaging.
Keywords: coronary artery aneurysm; giant aneurysm; Kawasaki disease